Importance of time-saving fine-needle aspiration cytology procedure in the diagnosis of sister Mary Joseph's nodule in the era of advanced technology - Shweta Joshi-Warpe; Bhushan M Warpe (Wolters Kluwer Medknow Publications, 2018)
The umbilicus is an uncommon site of cutaneous metastasis called as Sister Mary Joseph's nodule (SMJN), which is associated with grave prognosis. The most common primaries are the colon and stomach in males and ovaries and endometrium in females. We present a case of an elderly male with indurated umbilical swelling, unguided fine-needle aspiration cytology (FNAC) of which revealed umbilical metastasis (SMJN). On subsequent extensive work-up, this case was diagnosed as primary gastric adenocarcinoma on relevant gastric biopsy. This highlights the cost-effectiveness, time-saving diagnosis with the usage of FNAC procedure in such umbilical nodule cases, which are later confirmed on histopathology.